MENINGKATKAN HASIL BELAJAR MELALUI METODE VALUE CLARIFICATION TECHNIQUE (VCT) - Ahmad Ahmad (Jurnal Ilmiah Tarbiyah Umat, 2023)
This research is Classroom Action Research (CAR) which deals with problems namely; Can the Value Clarification Technique (VCT) method improve the learning outcomes of class V Talangga students in learning Civics about the Unitary State of the Republic of Indonesia? The purpose of this research is to describe the application of the Value Clarification Technique (VCT) method in learning civics education, especially in explaining the meaning of the Unitary State of the Republic of Indonesia (NKRI). The research subjects were fifth grade students at SD Negeri Talangga with a total of 35 students. The results showed that the application of the Value Clarification Technique (VCT) method in learning civics education, especially in material explaining the meaning of the Unitary State of the Republic of Indonesia (NKRI) can improve student learning outcomes at SDN Talangga as evidenced by the average pre-cycle test results of 63.50; Cycle I 72.10 and Cycle II 86.